Seasonal changes of body height and weight increments in school-children - Jelisiejew, Tamara; Gopaniuk, Zbigniew (Anthropological Review, 1980)
As a material for this study served longitudinal measurements taken over a period of two years on 155 children attending classes with normal curriculum and 167 children from classes having increased amount of physical education in their curricula. Age of 5th grade children at the beginning of the study was 11.5 years and those of 6th grade 12.5 years. Measurements were taken for the first time in October 1974 and repeated every May and October. In the present paper results of the first measurements are given along with information on semi-annual increments. The characters studied were: body height, body weight and a motoric trait — swiftness. It has been found that increments in body height are regular: as a rule increases during spring (May) were larger than those in October. This rythm has been observed in both "normal classes” children and children subject. to increased amount of physical education courses (see fig. 1 and 2). With respect. to the body height a seasonal rythm has been observed only in children from Białystok City exposed to intense physical education schedule (see fig. 4 and 3). In the same group of children also a rythm of increases in swiftness has been. found, in this case increments being larger in May than in October.